Implementation of Lesson Study in Learning Process: A Study of Biology Student Learning Activities - Muh. Nur Akbar; Aida Fitriyatur Rohma; Allvanialista Ikalor (Journal Of Biology Education Research (JBER), 2022)
Prospective student educators can use Lesson Study to improve their ability to plan and design learning. However, understanding of the implementation of Lesson Study in the learning process by 1st semester students at the Postgraduate Biology Education Study Program, Universitas Negeri Malang are still lacking. Thus, a study or research is necessary for the implementation of Lesson Study by students. This study aims to determine student learning activities through the application of Lesson Study and as a form of training for students to transform their knowledge as prospective educators. Descriptive qualitative research is the type of research conducted here. There were three stages to this research, namely planning, implementing, and reflecting. The data obtained from this study are the implementation of Lesson Study activities with the application of the Jigsaw type cooperative learning model, the implementation of Lesson Study activities with the application of the STAD cooperative learning model combined with Snowball Throwing, student learning activities, and the results of reflection on the implementation of Lesson Study. According to the study's findings, Lesson Study can accurately reflect student activities and its implementation in the learning process is also able to provide prospective educators with an understanding of pedagogical competence.